SALIVARY TUMOR NECROSIS FACTOR-ALPHA (TNF-Α)-A POTENTIAL MARKER OF PERIODONTAL DESTRUCTION. EVOLUTION UNDER DOXYCYCLINE TREATMENT - Ioana Martu; Ionut Luchian; Ancuta Goriuc; Dana Budala; Alexandra Martu; Monica Tatarciuc; Cristian Martu; Alexandra Jitareanu (Romanian Dental Association for Education, 2020)
Periodontal disease is an inflammatory condition caused by the accumulation of bacteria on tooth surfaces as oral biofilms. Cytokine production is increased in the gingival fluid and in tissues affected by periodontal disease, and their level is important for the diagnosis of periodontal diseases, but also for their prognosis. Salivary levels of cytokines (TNF-α) can represent reliable markers for evaluating the therapeutic outcome of different treatments for periodontitis, for example, systemic doxycycline administration. Aim: to determine the salivary concentrations of TNF-α, as a disease marker, in patients with aggressive (AgP) and chronic (ChP) periodontitis, before and after treatment with doxycycline. Material and methods: 20 patients were distributed into 2 groups: 8 diagnosed with AgP, 12 with ChP periodontitis. TNF-α level was determined using the ELISA technique in the patients' saliva before and after systemic doxycycline (Dox) treatment. Results and discussions: The salivary TNF-α levels were elevated in both chronic and aggressive periodontitis patients when compared with healthy individuals. The average drop in TNFα values after doxycycline administration was higher for aggressive periodontitis patients. Conclusions: According to our results, we could conclude that TNF-α may be regarded as diagnostic markers of periodontitis. Doxycycline treatment, in terms of lowering TNF-α levels was most effective in patients with aggressive periodontitis.